ANALISIS KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI YANG TERCATAT DI BURSA EFEK INDONESIA - Repon, Rezky Rahman (Department of Management, 2014)
This research is descriptive nature of case study research analytical tool used to determine and analyze the financial performance of telecommunications companies listing in BEI using EVA analysis. Assessment of financial performance is measured with the provision that if EVA ? 0, then provide economic value added to the company , if EVA ? 0 , then it does not give the company's.EconomicValueAdded.Based on the analysis of financial performance of telecommunications companies listed in Indonesia Stock Exchange fluctuated , In 2010 PT XL Xiata Tbk and PT Inovisi Infrcom tbk give Economic Value Added . In 2011, PT XL Xiata Tbk , PT Indosat Tbk , and PT Infracom Tbk , and PT Telekomunikasi Indonesia Tbk otherwise provide Economic Value Added and the year in 2012 Infracom PT Tbk and PT Indosat Tbk otherwise provide Economic Value Added ( EVA)?0.Telecommunications companies that provide the greatest economic value added in 2011 was PT Telekomunikasi Indonesia tbk Based on the above conclusions , the authors recognize that these results are still far from perfect , due to the limitations of both the data and the object of research , because it is necessary for other researchers conducted research on EVA by using a longer period of study or research use another object. Keywords: Economic Value Added, Financial Performance, telecommunication Companies